Existence and Uniqueness of Solutions for Boundary Value Problems to the Singular One-Dimension p-Laplacian. (4th February 2008) - Lin, Xiaoning; Sun, Weizhi; Jiang, Daqing
Abstract : In this paper, We study the existence and uniqueness of solutions for boundary value problems to the singular one-dimensionp -Laplacian by using mixed monotone method. Our results improve several recent results established in the literature.